Nano Formulations Targeting the Brain: Advances in Drug Delivery Systems for Cognitive Dysfunction in Depression - Jerin James; Jamuna Rani; Sathyanarayanan Varadarajan (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
The article focuses on various nanotechnological approaches employed to overcome the blood-brain barrier (BBB) and facilitate targeted drug delivery to the brain, which is the crux in the management of cognitive disorders. Major depressive disorder is a widespread neuropsychiatric condition that often goes unnoticed and undiagnosed, particularly in underserved populations lacking access to healthcare. Studies have demonstrated that the pathophysiology of depression involves dysfunctions in the dominant glutamatergic system, impairments in mechanisms regulating glutamate clearance and metabolism, as well as morphological and maladaptive changes in brain regions associated with cognitive-emotional behaviors. Cognitive dysfunction is a prominent aspect of depression, with no new approved drugs for its management since vortioxetine. Consequently, the development of nanoformulations with enhanced brain permeability, sustained action, and superior efficacy represents a promising future direction. This comprehensive review provides an updated summary of recent advancements in the field of nanomedicines and nano-based drug delivery systems, highlighting their potential for enhancing the efficacy of both novel and existing drugs in the treatment of cognitive dysfunction in depression. Additionally, the review highlights recent studies utilizing nano-based formulations for delivering drugs targeting the glutamatergic system, such as NMDA receptor modulators, neuroprotective agents, and neurotrophic factors. The potential of nanomedicines in restoring glutamate homeostasis, improving synaptic plasticity, and enhancing neurogenesis is discussed. Moreover, the review discusses the advantages of nanocarrier-based strategies in improving drug pharmacokinetics, reducing side effects, and providing sustained drug release profiles, thereby enabling improved therapeutic outcomes and patient compliance.